Desfechos perinatais de mulheres acompanhadas na atenção primária à saúde - Andriely Guedes Saturnino; Camila Moraes Garollo Piran; Alana Vitória Escritori Cargnin; Bianca Machado Cruz Shibukawa; Maria de Fátima Garcia Lopes Merino; Marcela Demitto Furtado (Revista Feridas, 2022)
Objective: to evaluate the perinatal outcomes of women followed up in Primary Health Care in a city in northwest Paraná between 2019 and 2020. Method: this is a descriptive and exploratory study, with a quantitative approach, with women who underwent prenatal care at the Basic Health Unit. Data were collected through electronic medical records and telephone interviews. A questionnaire was applied about maternal sociodemographic characteristics, aspects of the current pregnancy, and characteristics of childbirth and newborns. Data analysis was performed using descriptive statistics. Results: the newborns had adequate weight and gestational age, in addition to the absence of deaths. However, some outcomes need to be further investigated, such as high cesarean section rates. Conclusion: deliveries 2 perinatal deliveries were prenatal among women who encompass the UBS of northwest Paraná019 and 2020 maternal as sociodemographic characteristics, as for newborns and newborns.